A ginástica na educação física escolar de estudantes universitários da Universidade Estadual Paulista/Campus de Rio Claro - Porto, Jaqueline [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Gymnastics is a manifestation of body culture, which has a number of fields (SOUZA, 1997): competition, demonstration, physical conditioning, body awareness and rehabilitation, providing a wide range of knowledge to be presented in physical education. But according to studies conducted by Nista- Piccolo (1988), Polito (1998), Barbosa (1999), Paoliello (2001), Ayoub (2003), Schiavon; Piccolo (2006) knowledge involving gymnastics has been tentatively applied in school. Therefore it is intended to research investigating the experiences of students with gymnastic contents of Physical Education, Universidade Estadual Paulista / Campus Rio Claro. Aiming at the students' perception regarding fitness classes they had in Physical Education. Participated in the survey 133 undergraduate students of Physical Education. On gymnastics experiences in basic education. If they did gymnastics, how often, what content, the materials used and how was that experience. Confirmed the initial hypothesis that the gym has been little applied in Physical Education. The research shows how important the training of future teachers of physical education, which influence other generations and that along with university education, their previous experiences lead to higher education, for Physical Education classes that minister future

A Ginástica é uma manifestação da cultura corporal, que possui vários campos de atuação (SOUZA, 1997): competição, demonstração, condicionamento físico, conscientização corporal e reabilitação, disponibilizando uma vasta gama de conhecimento a ser apresentado na educação física escolar. Porém segundo estudos realizados por Nista-Piccolo (1988), Polito (1998), Barbosa (1999), Paoliello (2001), Ayoub (2003), Schiavon; Piccolo (2006) conhecimentos envolvendo a Ginástica tem sido timidamente aplicado na escola. Por isso pretende-se com a pesquisa investigar as experiências com conteúdos ginásticos dos alunos do curso de Educação Física da Universidade Estadual Paulista/Campus Rio Claro, visando à percepção dos mesmos em relação às aulas de Ginástica que tiveram na Educação Física escolar. Participaram da pesquisa 133 graduandos do curso de Educação Física. Sobre as experiências Ginásticas no ensino básico: se fizeram Ginástica, com qual frequência, quais conteúdos, os materiais utilizados e como foi essa experiência. Confirmou-se a hipótese inicial de que a Ginástica tem sido pouco aplicada na Educação Física Escolar. A pesquisa revela como é importante a formação dos futuros professores de Educação Física, que influenciarão outras gerações e que juntamente com a formação universitária, levam suas experiências anteriores à formação superior, para as aulas de Educação Física que ministrarão futuramente
Keywords: Universidade Estadual Paulista Júlio de Mesquita Filho; Ginástica; Educação física - Estudo e ensino; Professores de educação fisica; Professores - Formação; Rio Claro (SP)